English and Algerian Legal Cultures Formation: A Comparative Anthropological Study - Mansouri, Mohamed Charif (Indonesian Journal of Social Science Research, 2024)
Legal cultures dissimilarities are likely to generate challenges at many levels, especially when they imply historical accumulations. The present literature review paper aims at discussing the diachronic development of the English and the Algerian legal cultures, revealing how such divergence has led to some repercussions. The research first uses historical and comparative approaches regarding legal institutions and professionals’ titles and then addresses current issues. The English legal culture has gone through four main periods, especially after the Norman Conquest in 1066 AD, and the Algerian one has been shaped across three principal stages, particularly in the post-independence era. The paper shows how the chronological development of the Algerian legal system was characterised by legal pluralism, especially the interaction between French Civil Law and Algerian Islamic Courts. It then discusses convergence issues between the English and Algerian legal systems in the globalisation era. It also looks at how the dissimilarities and rapprochement of legal cultures hold sway on a threefold anthropological parameter: social for the English, intercultural for the Algerians, and translational for both communities. At the social dimension, legalese is likely to create communicative problems for English neophytes. At the intercultural level, the dissimilarity of legal systems threatens the social identity of Algerian law students through self-enculturation contradiction, known as the continental paradox. At the translational level, the divergence gives rise to pitfalls in English-Arabic-English legal translation between the two contrasting systems, whereas the convergence, under the auspices of globalisation, needs the recourse to new methods.